2018
DOI: 10.1002/cctc.201800371
|View full text |Cite
|
Sign up to set email alerts
|

Selective Glucose‐to‐Fructose Isomerization over Modified Zirconium UiO‐66 in Alcohol Media

Abstract: Modulated zirconium metal–organic framework UiO‐66 is shown to catalyze the isomerization of d‐glucose to d‐fructose in alcohol media. Fructose selectivity can change depending on solvent choice. We hypothesize that the difference in selectivity is related to a combined effect of adsorption and solvation effects, which may lead to the high formation of alkylglucosides in depletion of fructose if methanol or ethanol are used. A fructose selectivity of 72 % at 82 % glucose conversion in 1‐PrOH was achieved. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 57 publications
(79 reference statements)
1
50
0
Order By: Relevance
“…This may indicate that glucose does not enter the pores of UiO‐66 and instead reactions are taking place on the outer surface of the material. Indeed, recent work by de Mello and Tsapatsis suggests that glucose is unable to enter the structure of un‐modulated UiO‐66, i. e. UiO‐66 that does not have missing Zr clusters [5g] . The nano and ultra‐nano materials generated higher quantities of fructose, mannose and HMF than UiO‐66.…”
Section: Resultsmentioning
confidence: 99%
“…This may indicate that glucose does not enter the pores of UiO‐66 and instead reactions are taking place on the outer surface of the material. Indeed, recent work by de Mello and Tsapatsis suggests that glucose is unable to enter the structure of un‐modulated UiO‐66, i. e. UiO‐66 that does not have missing Zr clusters [5g] . The nano and ultra‐nano materials generated higher quantities of fructose, mannose and HMF than UiO‐66.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, MIL-101(Cr) had been used as a host for phosphotungstic acid, thereby adding Brønsted acidity for carbohydrate dehydration [28], while most recently, Guo et al found that a composite of MIL-101(Cr) and chromium hydroxide gave superior isomerisation of glucose to fructose in ethanol solvent via ethyl fructoside that required hydrolysis in a second step [29]. Other MOFs that have been used for glucose conversion include the zirconium-based NU-1000, with phosphate modification to induce Lewis acidity [30], and the zirconium material UiO-66 with sulfo-modified ligands and inherent Lewis acidity from defects notably allowing conversion of glucose to fructose, along with a significant amount of 5-HMF in water alone [31], and selective conversion of glucose to fructose with iso-propanol solvent [32]. Sulfonated UiO-66 has been further tuned to optimise activity towards glucose conversion [33], compared with other zirconium MOFs [34], and has also been used to effect the esterification of levulinic acid with ethanol [35].…”
Section: Introductionmentioning
confidence: 99%
“…Also, glucose can be directly obtained from the abundantly available and cheaper lignocellulosic substances, which contain nearly 40 % cellulose [3] . However, converting glucose to fructose to produce 5‐HMF is a challenging step due to their equilibrium characteristics [4] . Moreover, an effective glucose conversion to 5‐HMF demands varying operating conditions to promote isomerization and dehydration reactions.…”
Section: Introductionmentioning
confidence: 99%